TINJAUAN TEORITIS PENGHASILAN TIDAK KENA PAJAK (PTKP) BERDASARKAN UNDANG-UNDANG NO. 36 TAHUN 2008 MENGENAI PAJAK PENGHASILAN DIBANDINGKAN DENGAN UPAH MINIMUM PROVINSI DKI JAKARTA SESUAI DENGAN PERATURAN GUBERNUR DKI JAKARTA NO. 176 TAHUN 2014 TENTANG UPAH MINIMUM PROVINSI DKI JAKARTA. (Studi Kasus Di Wilayah Jakarta) - Widiyanti Widiyanti (Universitas Pamulang, 2017)
Case Studies In Jakarta area.The role of government is indispensable, especially in bridging the interests of employers and workers' interests in order to determine the minimum wage. Welfare workers a barometer of whether the government through its policy succeeded in protecting the workers or not. In this study consists of two main issues, first is in connection with wage policy in Indonesia, especially against the Provincial Minimum Wage in accordance with the regulations of Jakarta Governor of Jakarta No. 176/2014 on Minimum Wages of Jakarta as well as in accordance with the legislation ketenegakerjaan, and its implementing regulations. The second is the amount of non-taxable income (taxable income) is already considering Living Needs of the taxpayer. The method used in the study is a descriptive analysis of the juridical approach. Data collection techniques used is literature study. Results of the research that wage policy in Indonesia has not been based on the need for decent living this can be seen from the determination of the magnitude of the Provincial Minimum Wage in the regulation of the Governor of DKI Jakarta No. 176 year 2014 does not meet the needs of a decent life. When compared to the results of a survey of the amount of Indonesian Trade Union Confederation in 2015. Determination exemption regulated Law No. 36 year 2008 Article 7, paragraph 3 and Rule Execution contained in the finance minister's regulation No.122/PMK.010/2015 on the adjustment of the amount of exemption not take into account the magnitude of the Living Needs decent is not enough to meet the needs of decent living individual taxpayer, although the method of calculating the amount of non-taxable income (taxable income) is already considering the prices and inflation. This is due to a period of change in the amount of non-taxable income (taxable income) can not follow the price increases and inflation. This means that wage policy is not in accordance with the Living Needs and nor reflect the aspirations of workers / employees to earn enough for their well-being with the family.